Leapfrogging with technology: introduction of a monitoring platform to support a large-scale Ebola vaccination program in Rwanda - Paula Mc Kenna; Serge Masyn; Annik Willems; Anne De Paepe; Romain Rutten; Jean Baptiste Mazarati; Felix Sayinzoga; Etienne Karita; Jean Nepo Nduwamungu; Amelia Mazzei; Julien Nyombayire; Rosine Ingabire; et al. (Taylor & Francis Group, 2021)
Continued outbreaks of Ebola virus disease, including recent outbreaks in the Democratic Republic of the Congo (DRC), highlight the need for effective vaccine programs to combat future outbreaks. Given the population flow between DRC and Rwanda, the Rwanda Ministry of Health initiated a preventive vaccination campaign supported by a vaccination monitoring platform (VMP). The campaign aimed to vaccinate approximately 200,000 people from Rwanda's Rubavu and Rusizi districts with the two-dose vaccine regimen Ad26.ZEBOV, MVA-BN-Filo. The VMP encompassed: biometric identification (iris scanning), mobile messaging, and an interactive reporting dashboard. The VMP collected data used to register and identify participants at subsequent visits. Mobile message reminders supported compliance. To 13 November 2020, the campaign was half complete with Ad26.ZEBOV administered to 116,974 participants and MVA-BN-Filo to 76,464. MVA-BN-Filo should be given to participants approximately 8 weeks after the Ad26.ZEBOV with a compliance window of −14 and +28 days. Of the 83,850 participants who were eligible per this dosing window for the subsequent MVA-BN-Filo vaccine, 91.2% (76,453/83,850) received it and 82.9% (69,505/83,850) received it within the compliance window defined for this campaign. Utilization of the VMP was instrumental to the success of the campaign, using biometric technology, dashboard reporting of near real-time data analysis and mobile phone communication technology to support vaccine administration and monitoring. A comprehensive VMP is feasible in large-scale health-care campaigns, beneficial for public health surveillance, and can allow effective response to an infectious disease outbreak.